Pengaruh Fisioterapi terhadap Penurunan Nyeri pada Pasien Rheumatoid Artritis di Klinik Fisioterapi Kota Jambi - Yuliana Yuliana; Kamariyah Kamariyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Rheumatoid Arthritis sufferers nationally in Indonesia are dominated by someone who has entered the age of Pre-elderly to the elderly in the age range between 55-64 years (15.5%), 67-74 years (18.6%), and ages above 75 years is at the number (18.9%), when totaled between the pre-elderly age up to 53% suffering from Rheumatoid Arthritis (Riskesdas 2018). Rheumatoid arthritis is a joint disease that occurs due to an autoimmune disorder that causes inflammation of the joints that causes pain, heat, stiffness, weakness. The solution offered to prevent this from happening is to provide physiotherapy to the aching joints. The goal is to reduce pain levels in patients undergoing physiotherapy at a physiotherapy clinic. The research method used in this study is quantitative, with a sample of 60 people, the method used is Pre Experimental Design with Pre Test and Post Test One Group design with intervention given to patients measured at each stage of physiotherapy. Research Results: Most of them are male (53.33%). Most of them are adults and elderly (35%) The description of the patient's pain level before physiotherapy is done, all patients experience pain, most of which are on a moderate to severe scale. After doing physiotherapy on T1 severe pain became 0%, and mild pain was 21.67%, on T2 mild pain was 6.67% and no pain was no pain 13.33%, while T3 was mostly in the no pain category (68.33%). The results of the statistical test obtained a p-value of 0.000. It can be concluded that physiotherapy is very effective in reducing pain levels in patients with pain rheumatoid artritis.